Spectrum access options for vertical network service providers in 5G. (May 2020) - Vuojala, Heli; Mustonen, Miia; Chen, Xianfu; Kujanpää, Kaisa; Ruuska, Pekka; Höyhtyä, Marko; Matinmikko-Blue, Marja; Kalliovaara, Juha; Talmola, Pekka; Nyström, Anna-Greta
Abstract: 5G will extend the mobile technology deployment beyond the communications industry, bringing connectivity to the explosively growing number of devices and services. To be able to respond to 5G sectors' different requirements, as well as the spectrum scarcity issue, different spectrum access approaches need to be considered. The aim of this article is to identify substantial properties of spectrum access approaches to assess their suitability to 5G vertical use cases. We have defined five optional spectrum access scenarios for 5G vertical network service providers (VNSPs) in acquiring spectrum access to provide a network service to either end users or other companies. The stakeholders involved in the spectrum awarding process are identified, and their roles and targets are examined. Furthermore, the advantages and drawbacks of each scenario are covered. Following the discussion, we were able to highlight some substantive characteristics in terms of suitability assessment, namely reliability, locality and mobility, mobile network operators (MNOs) involvement, costs and time scale. These characteristics were analysed in terms of each scenario to further the scenario's suitability assessment to VNSPs' purposes. Highlights: 5G will open up new possibilities to new entrants to enter wireless connectivity markets. Paper reviews different spectrum access options to meet the 5G vertical sectors' requirements. Versatile spectrum access options need to be made available to boost vertical network service provider businesses.